2023
DOI: 10.1021/acs.biomac.3c00916
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Surface Decoration of Phenylboronic Acid onto Natural Killer Cells for Sialic Acid-Mediated Versatile Cancer Cell Targeting

Ashok Kumar Jangid,
Sungjun Kim,
Hee Won Park
et al.

Abstract: Phenylboronic acid (PBA) has been highly acknowledged as a significant cancer recognition moiety in sialic acidoverexpressing cancer cells. In this investigation, lipid-mediated biomaterial integrated PBA molecules onto the surface of natural killer (NK) cells to make a receptor-mediated immune cell therapeutic module. Therefore, a 1,2-distearoyl-sn-glycero-3phosphorylethanolamine (DSPE) lipid-conjugated di−PEG−PBA (DSPE PEG -di(PEG−PBA) biomaterial was synthesized. The DSPE PEG -di(PEG−PBA) biomaterial exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This approach enables the augmented NK cell activation without the requirement of additional supplementary cytokine cocktails. Our results demonstrated that (1) TL modules could be effectively immobilized into the lipid bilayers of NK cell membranes, specifically via hydrophobic interaction [33,34], and (2) they could strengthen the membrane connections of NK cells through material-mediated physical links. In consequence, as compared with naturally-driven NK clustering, which is mediated by ECM production (without the aid of biomaterials), a significant induction of multiple membrane interactions occurred, leading to rapid and tight formation of NK cell clusters, and effective cell priming ultimately took place, resulting in enhanced IFN-γ secretion in TLNK spheroids.…”
Section: Discussionmentioning
confidence: 78%
“…This approach enables the augmented NK cell activation without the requirement of additional supplementary cytokine cocktails. Our results demonstrated that (1) TL modules could be effectively immobilized into the lipid bilayers of NK cell membranes, specifically via hydrophobic interaction [33,34], and (2) they could strengthen the membrane connections of NK cells through material-mediated physical links. In consequence, as compared with naturally-driven NK clustering, which is mediated by ECM production (without the aid of biomaterials), a significant induction of multiple membrane interactions occurred, leading to rapid and tight formation of NK cell clusters, and effective cell priming ultimately took place, resulting in enhanced IFN-γ secretion in TLNK spheroids.…”
Section: Discussionmentioning
confidence: 78%